The Effect Of Transformational Leadership And Compensation On Employee Performance Through Job Satisfaction As An Intervening Variable At PT. Adi Satria Abadi In Yogyakarta - Nur Wahidah; Trias Setiawati (UNIVERSITAS PAKUAN, 2024)
This study aimed to determine whether there is a mediating effect of job satisfaction in the relationship between transformational leadership and compensation on employee performance at PT. Adi Satria Abadi in Yogyakarta. This study uses a quantitative method and uses a questionnaire as a method of data collection. The population of this study was 200 employees. The sampling technique was carried out using the census method on all employees in the production department with a sample size of 170 employees. The research analysis method used the t-test, F-test, simple and multiple linear regression analysis, and path analysis. The results of this study reveal that transformational leadership has a positive and significant effect on employee performance, compensation has a positive and insignificant effect on employee performance, transformational leadership has a positive and significant impact on job satisfaction, compensation has a positive and significant effect on job satisfaction, job satisfaction has a positive and significant impact on employee performance, job satisfaction can significantly mediate the relationship between transformational leadership and employee performance, and job satisfaction can significantly mediate the relationship between compensation and employee performance.